2018
DOI: 10.18203/2320-6012.ijrms20183658
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of role of genetic polymorphisms in XRCC1, XRCC2 and XRCC3 genes in cervical cancer susceptibility from a rural population: a hospital based case-control study from Maharashtra, India

Abstract: Background: Cervical cancer is a major concern of health risk, moreover the leading cause of cancer causing deaths in women of rural parts of India. This study was aimed to assess the risk of cervical cancer development in association with polymorphisms in X-Ray Cross Complementing Group (XRCC1, XRCC2 and XRCC3) genes in the rural population of south-western Maharashtra. We focused to determine the frequency of polymorphisms in DNA repair genes including XRCC1 at codon (cd) 194, cd 280, cd 399, XRCC2 at cd 188… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…In our investigation of the XRCC2 Arg188His and XRCC3 Thr241Met polymorphisms and their role in cancer development, we noted no association with the XRCC2 polymorphism, while the XRCC3 polymorphism exhibited a negative association, indicating a protective effect against GI cancer risk in the studied population. These findings were in accordance with previous Indian studies that reported no association of XRCC2 Arg188His polymorphism with cervical [ 22 ], nasopharyngeal [ 23 ], or breast cancers [ 24 ]. Similarly, the rs1042522 and rs28934571 SNPs of TP53 were comprehensively studied in relation to GI cancer risk [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our investigation of the XRCC2 Arg188His and XRCC3 Thr241Met polymorphisms and their role in cancer development, we noted no association with the XRCC2 polymorphism, while the XRCC3 polymorphism exhibited a negative association, indicating a protective effect against GI cancer risk in the studied population. These findings were in accordance with previous Indian studies that reported no association of XRCC2 Arg188His polymorphism with cervical [ 22 ], nasopharyngeal [ 23 ], or breast cancers [ 24 ]. Similarly, the rs1042522 and rs28934571 SNPs of TP53 were comprehensively studied in relation to GI cancer risk [ 25 ].…”
Section: Discussionsupporting
confidence: 93%